About the image of mother with child in fine arts. Part III (final). XVIII–XXI centuries - N. A. Makatsariya (Акушерство, гинекология и репродукция)
Here, issues related to envisioning mother holding a child in fine arts of XVIII–XXI centuries are discussed. Paintings of Vigee-Le Brun, Bouguereau, Monet, Klimt, Renoir, Dali, Rivera, Picasso are represented as well as works of Russian artists Vasnetsov, Vrubel, Kustodiev, Chagall, and modern painters Hanks and Berggren